Emergency department targeted screening for hepatitis C does not improve linkage to care - Houri, Inbal (World J Gastroenterol, 2020)
BACKGROUND: Hepatitis C virus (HCV) infection is a leading cause of chronic liver disease worldwide. New treatments for HCV revolutionized management and prompted the world health organization to set the goal of viral elimination by 2030. These developments strengthen the need for HCV screening in order to identify asymptomatic carriers prior to development of chronic liver disease and its complications. Different screening strategies have been attempted, most targeting high-risk populations. Previous studies focusing on patients arriving at emergency departments showed a higher prevalence of HCV compared to the general population. AIM: To identify previously undiagnosed HCV carriers among high risk emergency room attendees and link them to care for anti-viral treatment. METHODS: In this single center prospective study, persons visiting the emergency department in an urban hospital were screened by a risk factor-specific questionnaire. The risk factors screened for were exposure to blood products or organ transplantation before 1992; origins from countries with high prevalence of HCV; intravenous drug use; human immunodeficiency virus carriers; men who have sex with men; those born to HCV-infected mothers; prior prison time; and chronic kidney disease. Those with at least one risk factor were tested for HCV by serum for HCV antibodies, a novel oral test from saliva (OraQuick(®)) or both. RESULTS: Five hundred and forty-one participants had at least one risk factor and were tested for HCV. Eighty four percent of all study participants had only one risk factor. Eighty five percent of participants underwent OraQuick(®) testing, 34% were tested for serum anti-HCV antibodies, and 25% had both tests. 3.1% of patients (17/541) had a positive result, compared to local population incidence of 1.96%. Of these, 82% were people who inject drugs (current or former), and 64% served time in prison. One patient had a negative HCV-RNA, and two patients died from non-HCV related reasons. On review of past medical records, 12 patients were found to have been previously diagnosed with HCV but were unaware of their carrier state. At 1-year follow-up none of the remaining 14 patients had completed HCV-RNA testing, visited a hepatology clinic or received anti-viral treatment. CONCLUSION: Targeted high-risk screening in the emergency department identified undiagnosed and untreated HCV carriers, but did not improve treatment rates. Other strategies need to be developed to improve linkage to care in high risk populations.